Card Sort Method: Peningkatan Kemampuan Membaca Huruf Hijaiyah pada Pelajaran Al-Quran Hadits Siswa Kelas II A MIN 4 Gunungkidul - Umi Suryani (Jurnal Pendidikan Madrasah, 2019)
This study aims to improve reading ability through the card sort method in the Al-Quran Hadith study for class II A MIN 4 Gunungkidul Students. This research was conducted from February to March 2018 with 19 research subjects. The method of this research is Classroom Action Research (CAR) using two cycles consisting of four stages, namely: action planning, action implementation, observation (observation), and reflection. Based on the results of the research conducted in two cycles, applying the card sort method has increased the activity of teachers and students. The implementation of the learning process increases seen from the results of students' learning abilities in the efforts of teachers in improving the ability to read the Qur'an in class II. A has achieved completeness. This can be seen from the increase in the average grade in the first cycle, 75.5 up to 82.3 or up 6.8 points in the second cycle and classical completeness in the first cycle, 68.4% up to 84.2% in the second cycle or up 15.8. This means that classical completeness has achieved success, which is above 80%. Based on the results obtained, it is expected that teachers are more creative in applying the learning strategies of the Card Sort method because not all subjects and subject matter can be delivered through this learning model. Also, the teacher can determine and choose the right strategy in carrying out learning.